2014
DOI: 10.2139/ssrn.2405951
|View full text |Cite
|
Sign up to set email alerts
|

The Multi-Faceted Concept of Transparency

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Second, it showed that citizens’ knowledge and skills (proxied by their level of education) enhance the connection between transparency and political efficacy. This result emphasizes the importance of the demand-side dimension of transparency (Forssbaeck & Oxelheim, 2014), by showing that only people who are endowed with resources and skills that ease their access to information and its understanding (namely more educated people) can fully benefit from government transparency to effectively monitor policy makers and hold them accountable; therefore, the higher people’s education is, the greater the positive effect that government transparency produces on their external political efficacy. Conversely, information disclosure about government activities is less effective for citizens who show lower skills (lower education), because they do not have adequate tools to benefit from it, and, feeling a sense of discomfort, may prefer opacity to transparency.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…Second, it showed that citizens’ knowledge and skills (proxied by their level of education) enhance the connection between transparency and political efficacy. This result emphasizes the importance of the demand-side dimension of transparency (Forssbaeck & Oxelheim, 2014), by showing that only people who are endowed with resources and skills that ease their access to information and its understanding (namely more educated people) can fully benefit from government transparency to effectively monitor policy makers and hold them accountable; therefore, the higher people’s education is, the greater the positive effect that government transparency produces on their external political efficacy. Conversely, information disclosure about government activities is less effective for citizens who show lower skills (lower education), because they do not have adequate tools to benefit from it, and, feeling a sense of discomfort, may prefer opacity to transparency.…”
Section: Resultsmentioning
confidence: 73%
“…As transparency is a multifaceted principle (Forssbaeck & Oxelheim, 2014), there are a number of international transparency indexes, developed by scholars as well as by international organizations. Each index relies on a different conceptualization of the term.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations